2021
DOI: 10.1029/2020jc016670
|View full text |Cite
|
Sign up to set email alerts
|

Large Mesoscale Eddies in the Western Arctic Ocean From Satellite Altimetry Measurements

Abstract: Eddies in the Western Arctic play an important role in transporting heat and salt from the continental shelf to the deep basin (e.g., D 'Asaro, 1988;Manley & Hunkins, 1985). They are also linked to the redistribution of freshwater within the surface-stress-driven Beaufort Gyre (BG) and the BG's stabilization, contributing significantly to overall along-isopycnal mixing in the Arctic Ocean (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…At diameter scales of 1-15 km, cyclones strongly dominate over anticyclones, in agreement with historical field observations [1] and model results [8]. However, in the range of 15-30 km this difference is gradually vanishing, and for diameter values above 30 km we observe an approximate parity between them, in agreement with satellite altimetry results [24,40], with a slight dominance of anticyclones. Such a transitioning from dominating cyclones to anticyclones happens when the eddy size exceeds the Rossby deformation radius, i.e., when mesoscale eddies start to dominate over submesoscale, as earlier reported for open-ocean eddies in [22,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At diameter scales of 1-15 km, cyclones strongly dominate over anticyclones, in agreement with historical field observations [1] and model results [8]. However, in the range of 15-30 km this difference is gradually vanishing, and for diameter values above 30 km we observe an approximate parity between them, in agreement with satellite altimetry results [24,40], with a slight dominance of anticyclones. Such a transitioning from dominating cyclones to anticyclones happens when the eddy size exceeds the Rossby deformation radius, i.e., when mesoscale eddies start to dominate over submesoscale, as earlier reported for open-ocean eddies in [22,30].…”
Section: Discussionsupporting
confidence: 90%
“…Almost twice better spatial resolution of Sentinel-1 means that it may better resolve spatial patterns of fine-and small-scale dynamic features in the MIZ. The orbital design of two Sentinel-1 sensors allows sequential mapping of MIZ eddies on a daily regular basis which is critical to assess their dynamic properties and evolution [7], that was previously available only from altimetry observations of large mesoscale open-ocean eddies in the Arctic Ocean [24,40]. However, in this study, we do not consider kinematic properties of MIZ eddies which is a subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…The MOSAiC data are to make a central contribution to this activity. Another example of the joint modeling and observational effort is to examine sub-mesoscale and mesoscale eddy statistics, and to improve their parameterization using data and high-resolution modeling (e.g., Danilov et al, 2017;Kubryakov et al, 2021). A further aspect is to explore largescale dynamical structures in the surface ice and ocean flows (Wilson et al, 2021).…”
Section: Relation To Modelingmentioning
confidence: 99%
“…Detection of eddies from space is largely limited in the Arctic Ocean by the presence of sea ice and the eddies' small scales. In the open water, however, satellite altimetry can be used to detect large eddies (Kubryakov et al, 2021). von Appen et al ( 2016) demonstrated that along-track altimetry data can be used in the non-ice-covered ocean to obtain EKE estimates consistent with mooring-based estimates.…”
Section: Impacts Of Mesoscale Variability On Arctic Ocean Circulation...mentioning
confidence: 99%